Specificity of Lipoxygenase Pathways Supports Species Delineation in the Marine Diatom Genus Pseudo-nitzschia - Lamari, Nadia; Ruggiero, Maria Valeria; d’Ippolito, Giuliana; Kooistra, Wiebe H. C. F.; Fontana, Angelo; Montresor, Marina (PLOS ONE, 2013)
Oxylipins are low-molecular weight secondary metabolites derived from the incorporation of oxygen into the carbon chains of polyunsaturated fatty acids (PUFAs). Oxylipins are produced in many prokaryotic and eukaryotic lineages where they are involved in a broad spectrum of actions spanning from stress and defense responses, regulation of growth and development, signaling, and innate immunity. We explored the diversity in oxylipin patterns in the marine planktonic diatom Pseudo-nitzschia. This genus includes several species only distinguishable with the aid of molecular markers. Oxylipin profiles of cultured strains were obtained by reverse phase column on a liquid chromatograph equipped with UV photodiode detector and q-ToF mass spectrometer. Lipoxygenase compounds were mapped on phylogenies of the genus Pseudo-nitzschia inferred from the nuclear encoded hyper-variable region of the LSU rDNA and the plastid encoded rbcL. Results showed that the genus Pseudo-nitzschia exhibits a rich and varied lipoxygenase metabolism of eicosapentaenoic acid (EPA), with a high level of specificity for oxylipin markers that generally corroborated the genotypic delineation, even among genetically closely related cryptic species. These results suggest that oxylipin profiles constitute additional identification tools for Pseudo-nitzschia species providing a functional support to species delineation obtained with molecular markers and morphological traits. The exploration of the diversity, patterns and plasticity of oxylipin production across diatom species and genera will also provide insights on the ecological functions of these secondary metabolites and on the selective pressures driving their diversification.